Theoretical and Cognitive Understanding of the Content of Preschool Education in the System of Education - Nadiya Frolenkova (Pedagogical Discourse, 2013)
The article deals with theoretical and cognitive  understanding of the content of preschool education. Attention is concentrated on the conceptual apparatus of the content categories of preschool education: teaching describes the essence of the category of «educational content», it is the factors that directly affect the structure of the category «content pre-school education». The basic approaches are determining the content of these categories. The problem is analysed as to  modern national system of education.